Pharmacological consequences of the coexpression of BK channel α and auxiliary β subunits - Torres, Yolima P.; Granados, Sara T.; Latorre, Ramon (Frontiers in Physiology, 2014)
Coded by a single gene (Slo1, KCM) and activated by depolarizing potentials and by a rise in intracellular Ca2+ concentration, the large conductance voltage- and Ca+2-activated K+ channel (BK) is unique among the superfamily of K+ channels. BK channels are tetramers characterized by a pore-forming α subunit containing seven transmembrane segments (instead of the six found in voltage-dependent K+ channels) and a large C terminus composed of two regulators of K+ conductance domains (RCK domains), where the Ca2+-binding sites reside. BK channels can be associated with accessory β subunits and, although different BK modulatory mechanisms have been described, greater interest has recently been placed on the role that the β subunits may play in the modulation of BK channel gating due to its physiological importance. Four β subunits have currently been identified (i.e., β1, β2, β3 & β4) and despite the fact that they all share the same topology, it has been shown that every β subunit has a specific tissue distribution and that they modify channel kinetics as well as their pharmacological properties and the apparent Ca+2 sensitivity of the α subunit in different ways. Additionally, different studies have shown that natural, endogenous and synthetic compounds can modulate BK channels through β subunits. Considering the importance of these channels in different pathological conditions, such as hypertension and neurological disorders, this review focuses on the mechanisms by which these compounds modulate the biophysical properties of BK channels through the regulation of β subunits, as well as their potential therapeutic uses for diseases such as those mentioned above.